2017
DOI: 10.1016/j.arth.2016.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Alumina Delta-on-Alumina Delta Bearing in Cementless Total Hip Arthroplasty in Patients Aged <50 Years

Abstract: Our minimum 6-year follow-up results with the use of alumina delta ceramic-on-alumina delta ceramic bearings in patients aged <50 years suggest that cementless THA provides a high rate of survivorship without evidence of osteolysis or fracture of ceramic material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
3
15
0
1
Order By: Relevance
“…We observed one (0.3%) fracture of a 28-mm short-neck alumina Forte head at 4.5 years after the index THA, and no ceramic fracture in the Delta COC cohort. Our findings are consistent with those of Kim et al [32], who identified no Delta ceramic head or liner fracture at a mean of 13.1 years of follow-up. Ceramic fractures are usually associated with specific events, such as trauma, hip dislocation, or cup malposition (i.e., excessively abducted or anteverted cup angle) [7].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We observed one (0.3%) fracture of a 28-mm short-neck alumina Forte head at 4.5 years after the index THA, and no ceramic fracture in the Delta COC cohort. Our findings are consistent with those of Kim et al [32], who identified no Delta ceramic head or liner fracture at a mean of 13.1 years of follow-up. Ceramic fractures are usually associated with specific events, such as trauma, hip dislocation, or cup malposition (i.e., excessively abducted or anteverted cup angle) [7].…”
Section: Discussionsupporting
confidence: 93%
“…Squeaking was reported in 2% of hips in each group, with no hip being revised due to this phenomenon. Although our results are similar to those of previous reports [11, 32] on modern ceramic bearings, the 2% incidence of squeaking in our study was lower than the rate of 7.5% published recently by Hamilton et al [1]. The reason for this difference is unclear, but may be due to the influence of lower BMI in our series compared with Westerners.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…According to reports of the manufacturer (CeramTec GmbH, Plochin-gen, Germany) and Agency Nationale de Sécurité du Médicament et des Produits de santé, ceramic head fracture of Biolox ® Delta has been 10–100 times lower than third-generation ceramic which was 0.0013%–0.002% and ceramic liner fracture was slightly lower which was 0.025%–0.028% 21. And also, previous reports did not report any ceramic head fracture 2223. These results have made the fourth generation of CoC articulation as an attractive articulation of choice to treat young active patients who require long survival of THA.…”
Section: Discussionmentioning
confidence: 99%